2019
DOI: 10.1016/j.jad.2018.12.091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for bipolar disorder and psychopathology from childhood to early adulthood

Abstract: Background Studying the phenotypic manifestations of increased genetic liability for Bipolar Disorder (BD) can increase understanding of this disorder. Aims We assessed whether genetic risk for BD was associated with childhood psychopathology and features of hypomania in young adulthood within a large population-based birth cohort. Methods We used data from the second Psychiatric Genetics Consortium Genome Wide Association Study (GWAS) for Bipolar Disorder to construct a polygenic risk score (PRS) for each ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 68 publications
5
30
0
Order By: Relevance
“…To the extent that this may involve individuals without the disease in question, this mitigates the risk of reverse causation and drug effects, though other sources of confounding may not be excluded [106]. Samples such as the UK Biobank, the ALSPAC birth cohort, the ABCD study, and those available to the Enigma neuroimaging consortium are currently being explored in relation to genetic risk for psychiatric disorders [17,[107][108][109][110][111]. These studies can help identify endophenotypic markers of risk such as brain structure [112,113] and cognitive impairment [62,114] and developmental antecedents [115].…”
Section: Population Studiesmentioning
confidence: 99%
“…To the extent that this may involve individuals without the disease in question, this mitigates the risk of reverse causation and drug effects, though other sources of confounding may not be excluded [106]. Samples such as the UK Biobank, the ALSPAC birth cohort, the ABCD study, and those available to the Enigma neuroimaging consortium are currently being explored in relation to genetic risk for psychiatric disorders [17,[107][108][109][110][111]. These studies can help identify endophenotypic markers of risk such as brain structure [112,113] and cognitive impairment [62,114] and developmental antecedents [115].…”
Section: Population Studiesmentioning
confidence: 99%
“…That is, a number of patients classified as having MDD in our sample might be misdiagnosed BD patients with undocumented/undetected hypomanic symptoms. However, a recent study showed that BD-PRS was not associated with hypomania (19). In addition, all subjects in our study were diagnosed by experienced raters with the semi-structured clinical interview SCID-I, which is a valid instrument to detect hypomania symptoms.…”
Section: Bd-prs and Mddmentioning
confidence: 81%
“…To date, few studies have investigated phenotypes associated with genetic risk of BD utilizing BD-PRS (19,54). In this study, we uniquely investigated the role of psychopathology and high-risk factors in young adults for the development of BD using BD-PRS scores.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network medicine 13 is an emerging field that combines systems biology and network science to understand how genes interact in disease and health. For PNDs, coexpression networks [14][15][16] and genome-wide association studies 9,17,18 have unraveled molecular mechanisms and genomic variations related to these disorders. Many more small-scale studies have investigated the roles of specific genes in PNDs.…”
Section: Introductionmentioning
confidence: 99%